PRESCRIBING PATTERN OF ANALGESICS IN THE ORTHOPAEDIC DEPARTMENT OF A TEACHING HOSPITAL IN NORTH INDIA- AN OBSERVATIONAL STUDY - Dr. Semira; Dr. Tauseef Nazir; Dr. Farooq M; Dr. Mehreen Imran (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BackgroundPain management is a crucial aspect of orthopedic care, and analgesics play a central role in treatment. The prescribing patterns of analgesics vary due to factors such as patient characteristics, physician preferences, and institutional protocols. Understanding these patterns can help optimize pain management and minimize adverse effects. Aim: To assess the prescribing pattern of analgesics in the orthopedic department of a teaching hospital in north India. Methods: This prospective observational study was conducted by the department of Pharmacology in association with the department of Orthopedics at SKIMS Medical College and Hospital, Srinagar, India, from November 2022 to March 2023. A total of 200 indoor patients receiving analgesics for orthopedic conditions were included. Data on patient demographics, type and number of analgesics prescribed, route of administration, duration of therapy, and any adverse effects were recorded and analyzed.  Results: The most commonly prescribed analgesics were non-steroidal anti-inflammatory drugs (NSAIDs), with diclofenac (37%) and aceclofenac (28%) being the most frequently used. Etoricoxib was prescribed in 5% of cases, while paracetamol was co-prescribed in 25% of patients. Opioid analgesics, such as tramadol, were used in 5% of patients, mainly in cases of severe postoperative pain. The average duration of analgesic therapy was less than 7 days for the majority of patients (85%), with only 15% requiring extended therapy for chronic conditions or complications. In 65% of patients, analgesics were prescribed in combination with gastroprotective agents, reflecting a cautious approach towards NSAID use. Conclusion: The study highlights the predominant use of NSAIDs in orthopedic pain management, with paracetamol frequently co-prescribed. Opioid analgesics were reserved for severe pain, and combination therapies were used selectively; nevertheless, there is a need for regular monitoring of prescriptions to minimize adverse effects and promote rational analgesic use.